Pattern of Injuries in Railway Fatalities at Bowring and Lady Curzon Hospital, Bangalore - Vidusha Vijay; S. Venkata Raghava (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The Indian Railways, started over 167 years ago, is among the world’s largest rail network. In acountry like India, the railway network is ideal for long-distance travel and movement of bulk commodities,apart from being an energy efficient and economic mode of conveyance and transport. Although beneficialin a multitude of ways, railway fatalities are known to cause tremendous loss, in terms of human lives aswell as economic forfeiture.Methods and results: A 7-month prospective and descriptive type of autopsy study was conducted at theDepartment of Forensic Medicine and Toxicology, Bowring and Lady Curzon Hospital attached to ShriAtal Bihari Vajpayee Medical College and Research Institute, Bangalore. Out of 98 cases of railwayfatalities, maximum number of deaths belonged to 21- 30 years age group i.e., 33 cases (33.67%) with malepreponderance (88 cases – 89.79%). The Hindu community contributed to 54 cases (55.10%). Maximumcases occurred in the monsoon season (34 cases - 34.69%) and majority of victims were found dead at thescene (90 cases - 91.83%). The predominant manner of death was suicidal (49 cases - 50%) and the mostcommon cause for death was shock and hemorrhage (53 cases - 54.08%).Conclusion: Studies such as this, can help in better understanding of railway fatalities which can help policymakers in implementing counteractive measures to prevent accidental deaths, discourage suicidal deaths andto improve railway safety in general.